Correlation between Physical Activity and Depression in Community-Dwelling Older Adult Palestinians - Halaweh, Hadeel; Al-Khateeb, Amal; Rasheed, Aya; Tomeze, Layth; Sultan, Mohammad; Alqaissi, Ismail (Medical principles and practice, 2024)
Abstract Objective: Investigating the relationship between physical activity (PA) and depressive symptoms is a vital field of research globally. Nonetheless, this association remains unexplored in the context of older Palestinian adults, highlighting the need for additional research on this population. Therefore, this study aimed to examine the association between PA and depressive symptoms among older Palestinian adults. Subjects and Methods: A cross-sectional study was conducted in the West Bank/Palestine with 266 participants. Data were collected using a PA socio-cultural adapted questionnaire (PA-SCAQ), the EuroQuol-5Dimensions-5Levels measure, and the Geriatric depression scale (GDS-15). Independent sample t tests and ANOVA tests were used to investigate mean differences in PA and GDS-15 scores between groups. Furthermore, multiple linear regression analysis was used to examine the relationship between study variables and the impact of the independent variable (PA level) on depressive symptoms. Results: The mean age of the participants was 65.01 ± 8.02 years (range: 55–86), women 51.9%. Lower levels of PA and higher depressive symptoms were recorded among women, participants ≥65 years, and with recorded diagnosed disease (p < 0.05). The regression analysis showed a negative significant correlation between PA and GDS-15 scores (β = −0.235, p < 0.001), when controlling for age (model 2), and for age and sex (model 3), significant associations were recorded, respectively (β = 0.192, p = 0.002), and (β = 0.14, p = 0.015). Conclusion: Participants who recorded higher depressive symptoms had a lower level of PA; regular moderate-intensity aerobic exercises can contribute to prevent depression symptoms in older adults. Highlights of the StudyLevels of physical activity (PA) levels are negatively associated with depressive symptoms in older adults.Women and participants ≥65 years recorded lower PA and higher depressive scores.Participants with musculoskeletal disorders, particularly arthritis, recorded lower PA and higher depression scores.Incorporating moderate-intensity PA interventions into mental health promotion programs can contribute to prevent or treat depression in older adults.